Juvenile Pernicious Anaemia and Hypothyroidism. A Family Study - Oliver, R. A. M. (1969)
A man presented with the sudden onset of pernicious anaemia at the age of 21. He had been treated for hypothyroidism since the age of 6. His father and only paternal aunt were also found to have pernicious anaemia. Gastric and thyroid antibody studies showed one or more antibodies to be present in all three subjects, as well as in the patient's mother.